Virtual prototype and cosimulation applied to a 3 DOF Delta Parallel Manipulator for Kinematics & Kinetics Behavior Studies - Mesa Montoya, Carlos Andrés; Herrera Lopez, Marlon Jhair; Holguin Londoño, German Andrés (Scientia et Technica, 2018)
This work presents the kinetics and kinematics analysis for delta-3 parallel manipulator. Kinematics and Kinetics validation was performed with a virtual prototype cosimulation using Solidworks and Labview and considering experimental data from physical prototype testing. In respect to the same testing path, comparisons of kinematics results from physical prototype against data of both virtual prototype and theoretical model, corroborate that positions of mobile platform have similar values in respect to the global coordinate system. On the other hand, actuator torques of theoretical model and virtual prototype reported conservative behaviors, whereas the torque of the physical prototype presents lower requirements under the same conditions. Work in unison of these computational tools allows a coherent study of mechanical systems and a direct comparison of the theoretical model, physical prototype and virtual prototype.